Whistleblowers Need Not Apply. (12th November 2018) - Eisenstadt, Leora F.; Pacella, Jennifer M.
Abstract : Whistleblowers are severely disadvantaged when they apply for jobs. Many whistleblowers experience retaliation twofold—first, at their place of employment after they initially blow the whistle, and, second, on the job market for any subsequent employment. This negative trail follows whistleblowers, labeling them as disloyal, suspicious, and, ultimately, not ideal employees, and, thus, unable to find work. Current federal law largely ignores this problem, and protections for job applicants with whistleblowing histories have been severely lacking in some of the most prominent whistleblowing statutes. This article is the first to examine this glaring lack of legal protection as it pertains specifically to whistleblower job applicants by undertaking a comparative analysis of the retaliation protections available in a number of federal statutes and suggesting statutory reform based on that analysis. Specifically, this article draws comparisons between civil rights statutes, including Title VII of the Civil Rights Act of 1964, the Americans with Disabilities Act, and the Age Discrimination in Employment Act, which each provide expansive protections for job applicants, and the most prominent current federal whistleblowing statutes, the Sarbanes‐Oxley Act, the Dodd‐Frank Act, and the False Claims Act, which lack these protections. We conclude by recommending amendments to these federal whistleblowing statutes, arguing for specific retaliation protections and redress for whistleblowers who are denied a chance to work again because of their past revelations.